2022
DOI: 10.1097/meg.0000000000002409
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of biologic therapy in microscopic colitis: systematic review and meta-analysis

Abstract: Background This systematic review and meta-analysis sought to evaluate the effectiveness and safety of biologic therapy in the treatment of steroid-refractory microscopic colitis (MC). Methods We searched MEDLINE, Embase, Web of Science, and Cochrane Central to identify articles and abstracts reporting efficacy or safety data on biologic use (infliximab, adalimumab, certolizumab, golimumab, vedolizumab, ustekinumab, and tofacitinib) for induction and maintenance of remission in MC. We assessed clinical remis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Biologics such as anti-TNFs (infliximab and adalimumab) and integrin receptor antagonists (vedolizumab) have also been recommended as a treatment for steroid refractory microscopic colitis. A recent systemic review and meta-analysis showed a 100% clinical response at 3–6 weeks, dropping to 67% after 12–16 weeks [38 ▪▪ ,39]. The biologics used for treatment were infliximab, adalimumab and vedolizumab.…”
Section: Introductionmentioning
confidence: 99%
“…Biologics such as anti-TNFs (infliximab and adalimumab) and integrin receptor antagonists (vedolizumab) have also been recommended as a treatment for steroid refractory microscopic colitis. A recent systemic review and meta-analysis showed a 100% clinical response at 3–6 weeks, dropping to 67% after 12–16 weeks [38 ▪▪ ,39]. The biologics used for treatment were infliximab, adalimumab and vedolizumab.…”
Section: Introductionmentioning
confidence: 99%